2014
DOI: 10.1507/endocrj.ej13-0496
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of women with gestational diabetes mellitus by the new consensus criteria: two year experience in a single institution in Japan

Abstract: In 2010, International Association of Diabetes and Pregnancy Study Group (IADPSG) proposed new criteria for diagnosing and classifying gestational diabetes mellitus (GDM), based on data of the observational hyperglycemia and adverse pregnancy outcomes (HAPO) study [1]. Since the new diagnostic criteria would increase the frequency of GDM diagnosis without a detailed cost-effectiveness analysis, the number of health care associations implementing the new criteria is still limited [2]. Thus, there is a paucity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
4
26
1
3
Order By: Relevance
“…Firstly, patients were included since 2008 and were classified according to two different criteria for GDM diagnosis (Carpenter and Coustan and the IADPSG). Ikenoue et al suggested that the IADPSG-defined GDM of one abnormal OGTT value indicates a less severe glucose intolerance, but may still signal a risk of requiring insulin when a first-degree family history of diabetes exists [54]. Our participants had a high prevalence of a relative with diabetes (68.4 %).…”
Section: Discussionmentioning
confidence: 89%
“…Firstly, patients were included since 2008 and were classified according to two different criteria for GDM diagnosis (Carpenter and Coustan and the IADPSG). Ikenoue et al suggested that the IADPSG-defined GDM of one abnormal OGTT value indicates a less severe glucose intolerance, but may still signal a risk of requiring insulin when a first-degree family history of diabetes exists [54]. Our participants had a high prevalence of a relative with diabetes (68.4 %).…”
Section: Discussionmentioning
confidence: 89%
“…24,25 Whether in the latter studies the absence of differences in these two groups was the result of effectiveness of treatment or a lack of difference in prevalence of adverse outcomes independent of treatment cannot be inferred as a result of the lack of an untreated IADPSG GDM control group.…”
Section: Discussionmentioning
confidence: 98%
“…The universal initial screening for GDM assessed whether the pregnant women had the following clinical risk factors: (1) pre-gravid overweight (body mass index (BMI) ≥ 30); (2) past history of GDM; (3) past history of macrosomia (birth weight ≥ 4,000 g); (4) family history of type 2 diabetes in first-degree relatives; and (5) random plasma glucose ≥ 95 mg/dL [8]. Women with one or more risk factors underwent a diagnostic 75-g oral glucose tolerance test (OGTT) to measure plasma glucose (mg/dL) in the fasting state and at 1-h and 2-h after the glucose load.…”
Section: Methodsmentioning
confidence: 99%
“…The daily calorie count was calculated from the ideal body weight. GDM patients received 30 kcal/kg + 150 kcal in the early gestational stage and 30 kcal/kg + 350 kcal in the late gestational stage, according to the recommendations of Japan Diabetes Society and previous report [8]. Patients with GDM consumed calories three times a day in the hospital.…”
mentioning
confidence: 99%